P PENINGKATAN KEMAMPUAN BERBICARA SISWA SD DENGAN MENERAPKAN METODE BERMAIN PERAN - Debi Risnawati; Falma , Fris Okta (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to examine how applying the role-playing method can enhance speaking skills among elementary school students. The research method employed is a systematic literature review, which involves reviewing a variety of articles, journals, and literature related to the use of role-playing in language learning at the elementary school level. The research process started by defining the research problem, followed by searching for results from relevant journals for data analysis. Data collection was carried out online through platforms like Publish or Perish and Google Scholar. From this search, 10 articles were selected that were relevant to the topic. The gathered data was then analyzed using a qualitative descriptive approach. The findings indicate that the role-playing method is effective in improving students' speaking skills, increasing their confidence, and enhancing their xlearning outcomes.